Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3928/01477447-20170117-04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humeral Component Version on Outcomes in Reverse Shoulder Arthroplasty

Abstract: Although reverse shoulder arthroplasty provides excellent clinical results in appropriately selected patients, loss of external and internal rotation may occur. Component selection, design, and placement affect postoperative results. Recent studies considered the effect of humeral component version on functional results. The current study investigated whether humeral stem retroversion affects the outcomes of reverse shoulder arthroplasty with a retrospective review of a multisurgeon, industry-sponsored, prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Overall patient demographics of the three groups are described in Table 2. Seven studies with a total of 380 patients reported on RTSA where the humeral stem was implanted at less than 20 • of retroversion [14][15][16]24,27,28,30]. Of these studies, four were evidence level III, and three were level IV.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall patient demographics of the three groups are described in Table 2. Seven studies with a total of 380 patients reported on RTSA where the humeral stem was implanted at less than 20 • of retroversion [14][15][16]24,27,28,30]. Of these studies, four were evidence level III, and three were level IV.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There is a wide variation in practice as to the degrees of retroversion recreated, with biomechanical studies suggesting a compromise of avoiding scapular neck impingement by substituting a more anatomical version compared to increasing the range of motion, specifically external rotation, by implanting the stem in progressive degrees of retroversion [12,13]. Few clinical studies exist that have explicitly examined the effects of altering humeral stem version in RTSA on ROM and functional scores, with the current literature unable to show a distinct advantage of one particular version over another and no clear consensus from expert opinion [14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…24 Humeral component retroversion has been explored in multiple studies. [25][26][27] Placing the humeral component in up to 20 retroversion increases the tension in the posterior rotator cuff and therefore may improve force for external rotation while not restricting internal rotation. This is important as maintaining good rotational forces following RSA is a major challenge.…”
Section: Resultsmentioning
confidence: 99%
“… 16 In this study, humeral retroversion did not affect shoulder elevation unlike previous studies. 1 , 12 , 37 …”
Section: Discussionmentioning
confidence: 99%